The Effect of Internal Mutation on Performance Through Career Development and Work Motivation of Civil Servants at RSUD Nene Mallomo Sidenreng Rappang Regency - Fatmawaty M; Ansar; Syafri Aries S; Abdul Latief R; Syahruddin; Muhammad Yunus (MultiTech Publisher, 2024)
The purpose of this study was to determine, analyze, and describe the effect of internal mutation on career development, work motivation, and employee performance at RSUD Nene Mallomo Sidenreng Rappang regency, as well as to determine, analyze, and describe the effect of internal mutation on performance. A survey design with a quantitative approach was used in this study, while the research location was RSUD Nene Mallomo Sidenreng Rappang Regency where a sample of 140 employees was taken using a simple random technique from a population of 240 employees. The results showed that internal mutation directly had a significant positive effect on career development, work motivation, and employee performance at RSUD Nene Mallomo Sidenreng Rappang Regency. This study shows that the level of work motivation has a significant influence on improving performance, by motivating them to achieve goals and carry out their tasks more effectively. Internal mutation and career development, although still relevant, seem to have a more limited impact on influencing the performance of civil servants at RSUD Nene Mallomo Sidenreng Rappang Regency. Therefore, management strategies that focus on improving employees' work motivation may be considered more effective in improving the performance of civil servants.